Sleeping Beauty - Southgate, vera (London : Lady Bird Ltd)
Once upon a time a king and a queen lived and they wanted a child, but they could never have one. The situation started changing the day the queen met a frog that promised her that she would give birth to a girl in a year. The royal couple got a daughter, and they were so happy that they decided to throw a big party. They invited the fairies that lived in their kingdom to the christening. The custom was that each fairy wishes something beautiful for the child. Except for the mentioned fairies, everybody had forgotten an old one. Full of anger and hatred she went to the castle. The servants set up a table but they$1 (Bve only put 12 plates, and there were 13 fairies. The good fairies said their wishes and then the old one showed up. She said a horrible curse and threatened that the girl would stab herself at the age of 15 on a spindle and die.s
English Fiction Book
Keywords: English - Fiction Book